Imaging of patients suspected of having pulmonary thromboembolic disease; the value of chest x-ray combined with perfusion scan in South Africa - Teye, Samuel (My University, 2022)
Introduction: Even with recent technological advancement to improve medical diagnostics, diagnosing individuals suspected of having pulmonary thromboembolism remains difficult in medicine. A complete clinical examination, risk assessment, and imaging, including lung scintigraphy, are all needed to make a diagnosis. To diagnose pulmonary thromboembolism, lung scintigraphy uses a number of interpretation criteria. The PIOPED II criteria, which uses ventilation and perfusion images, the modified PIOPED II criteria, which uses chest x-ray, ventilation, and perfusion images, and the PISAPED criteria, which uses the chest x-ray and perfusion images, are among them. In acute pulmonary embolism, the primary goal of ventilation scanning as an adjunct to perfusion lung scintigraphy is to classify segmental perfusion defects as unmatched, which is widely regarded as proof of pulmonary embolism. Aim: To determine the value of a recent chest x-ray (done within 24 hours of the perfusion scan) combined with perfusion in diagnosing acute pulmonary thromboembolism in clinical settings. Method: Retrospective analysis of 155 consecutive patients clinically suspected with pulmonary thromboembolism between January 2017 and January 2019, who underwent a lung perfusion study. Results: Most of the study participants (75.5%) were Black. The overall population studied had a mean age of 50.09 years (SD 16.78). A recent chest x-ray was found in 40.1% of the projected sample size of 386 people, with 98% of them being of suboptimal quality. The sensitivity and specificity of the PISAPED 1 reader were 96% and 97%, respectively, with an NPV and PPV of 99% and 89%. The sensitivity and specificity of the PISAPED 2 reader were both 96%, with a NPV and PPV of 86%and 99%, respectively. The PIOPED II and the PISAPED 1 had an agreement of 88.39% (Kappa value of 0.7348) while the PIOPED II and the PISAPED 2 had an agreement of 88.39% (Kappa value of 0.7348). Conclusion: Chest x-ray in conjunction with perfusion scintigraphy is accurate and can reliably replace ventilation/perfusion scintigraphy in the diagnosis of pulmonary embolism.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022